A bibliometric analysis of natural disasters and business management in tourism - Chen, Shuixia; Xu, Zeshui; Wang, Xinxin; Škare, Marinko (Journal of Business Economics and Management, 2022)
Natural disasters are a critical factor for the development of business management in the tourism industry, leading to an increasing number of publications on the relationship between natural disasters and tourism business management (ND&T). In order to identify the research status of ND&T and explore the direction for future research, this paper collects 335 publications related to ND&T and develops a bibliometric analysis of the existing publications. First, we map the leading countries/regions, institutions, authors, and journals of ND&T to visualize the general analysis. Then the cooperation network is provided to show the collaboration relationship between countries/regions, institutions, and authors. Third, we introduce the keyword analysis to obtain research hotspots of ND&T. And finally, we explore the research theme analysis through literature review and conclude four topics. The findings of the topic analysis suggest that research on ND&T is receiving increasing attention, and more cooperation is required in the future to deepen the theoretical and empirical focus on tourists.